Does Targeting Really Work? The Perspective Of A Dominant Ethnic Group - Ernest Cyril, de Run (Universiti Malaysia Sarawak, (UNIMAS), 2005)
There have been numerous calls to target specific ethnic groups but there are a limited number of studies that show quantitatively the reaction of targeted groups. This study specifically sets out to demonstrate quantitatively the views of a dominant ethnic group towards adverts that target themselves, another non-dominant similar ethnic group, and a non-dominant non-similar ethnic group. It is noted that dominant ethnic groups have more positive reactions towards ads targeting themselves and using their language but react negatively to ads targeting other ethnic groups or using other language. Implications to companies are discussed and further research is suggested.